If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 1 = a + 1 Reorder the terms: 1 + 5a = a + 1 Reorder the terms: 1 + 5a = 1 + a Add '-1' to each side of the equation. 1 + -1 + 5a = 1 + -1 + a Combine like terms: 1 + -1 = 0 0 + 5a = 1 + -1 + a 5a = 1 + -1 + a Combine like terms: 1 + -1 = 0 5a = 0 + a 5a = a Solving 5a = a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 5a + -1a = a + -1a Combine like terms: 5a + -1a = 4a 4a = a + -1a Combine like terms: a + -1a = 0 4a = 0 Divide each side by '4'. a = 0 Simplifying a = 0
| x^2=81x | | 8(x-6)=5 | | 8(x-6)=0 | | x^2+17+20=0 | | 3x^2+35x-9.5=0 | | 25x^2-x=0 | | y^2+2y+20=0 | | -3x^2+27x=0 | | 7[9-7(8-b)]-9=9[7(9b-8)+6]-82 | | 17(3m+2)= | | 5x-7(x-8)=48 | | c=2.02w+15.83 | | 18(n+1)= | | (9x^3-4x^2-7)+(-2x^3-2x-4)=0 | | a^2+1=25 | | =5x^2-8x-4 | | =27x^2-90x+27 | | 9x^2+12x+4=12 | | (n+9)+1= | | =3x^2-x-2 | | x(-3x+7)=21 | | 5y+-3x=5 | | -x^2+4=9x+1 | | 7(x+4)= | | 9x+6=16x+8 | | 15-x=11 | | 12v^2=27 | | 2x-(x+12)=3x-10 | | 3x+9=6x+36 | | x-7=-8-2x | | 3(c+5)=8c-20 | | 6w+3=6.2+w |